Український аспект валашсько-російських відносин 1688–1700 рр. - Пономарьов, О. (Україна в Центрально-Східній Європі, 2013)
На основі опублікованих, а також архівних матеріалів розглянуто валасько-російські взаємини під час війни з Туреччиною у 1688–1700 рр. Зокрема, значну увагу приділено проблемі пошуку правителями Валахії нового протектора. Окремо виділено посередницьку роль гетьмана Івана Мазепи у таємному листуванні між Москвою та Бухарестом. На основе опубликованных, а также архивных материалов рассмотрено валашско-русские отношения во время войны с Турцией в 1688–1700 годах. В частности, значительное внимание уделено проблеме поиска правителями Валахии нового протектора. Отдельно выделено посредническую роль гетьмана Ивана Мазепы в тайной переписке между Москвой и Бухарестом. Topic of the Wallachian-Russian relations during the war with Turkey in 1688–1700 is actualized on the basis of published and unpublished archival materials. We pay attention to the problem of searching the new protector for Wallachia by rulers of this country. They were trying to find a defender who would be able to release the country from Ottoman domination and to insure its safety from the infringements of Austria. At the same time Wallachian territorial integrity, Orthodox religion, certain rights and freedoms had to be saved. Internal and external factors that influenced the policy of Wallachian proprietors Sherban Kantakuzino and Constantin Brancoveanu are identified in this research.